Peran TV Sekolah Sebagai Media Pembelajaran dan Komunikasi yang Efektif di RA Senyum Muslim - Neneng Yulianah; Sri Watini (LUGAS Jurnal Komunikasi, 2022)
This study describes the role of school TV as an effective learning and communication medium in RA Senyum Muslim. TV is a social media as a means of broadcasting in the form of images accompanied by sounds or sounds, so as to produce an interesting, entertaining and educational spectacle for children to adults. Fordorum School TV was developed by Dr. Sri Watini (CEO) Drs. Karnadi, MRDM (CIO) and Sigit W. Triwibowo, S.Sn (CTO). This School TV has several features including The School Stage, Digital Library, Virtual Classroom and School Bazaar is in the process of being developed. The role of School TV as an effective learning and communication medium in RA Senyum Muslim, is a very powerful medium (apowerful medium) in disseminating information to the public simultaneously. In addition, it has the potential for penetration in influencing attitudes, creativity, motivation, views, lifestyle, and orientation of society. In fact, last but not least, television broadcasts also have the potential to convey educational / learning messages. Thus, TV broadcasting is a form of learning and learning resources that can be used to improve the quality of education. This study was obtained by universal data collection techniques, observations and questions and answers to respondents at RA Senyum Muslim.